2017
DOI: 10.3390/w9090702
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Tufa Degradation in Jiuzhaigou National Nature Reserve, Sichuan, China

Abstract: Water and tufa samples were collected from Arrow Bamboo Lake, the stream from Panda Lake to Five-Color Lake, Pearl Shoal and Shuzheng Lakes in Jiuzhaigou National Nature Reserve, China, between October 2013 and September 2014, to investigate tufa growth rate and water environment (water temperature, pH, electric conductivity, major ions and nutrients), and analyzed to explore the main causes of tufa degradation. The mean annual rate of tufa growth was low and varied within lakes, with the maximum deposit thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Our surveys are consistent with observations from other national and international geoparks. Here, too, high-quality tufa landforms are attraction factors for high visitor numbers [26][27][28] but are also subject to increasing degradation and endangerment as a result [15][16][17]54,[62][63][64][65][66][67][68]. This is due to the high vulnerability of the Tufa landforms, particularly cascades and sinter basins [62,63].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our surveys are consistent with observations from other national and international geoparks. Here, too, high-quality tufa landforms are attraction factors for high visitor numbers [26][27][28] but are also subject to increasing degradation and endangerment as a result [15][16][17]54,[62][63][64][65][66][67][68]. This is due to the high vulnerability of the Tufa landforms, particularly cascades and sinter basins [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Calcerous tufa and sinter are among the most impressive natural spectacles in karst landscapes, whose scientific and aesthetic values are universally recognized [15][16][17][18][19][20][21][22][23][24][25]. They, therefore, attract a growing number of visitors [26][27][28] but are unfortunately extremely vulnerable and can be seriously damaged even by minor inference. The rediscovery of the "Heimat" (homeland), associated with a significant increase in visitors to natural areas led to negative repercussions for the environment [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water in the valleys mainly comes from precipitation, mountain meltwater and underground karst water. Travertine is a type of calcium carbonate deposit [38] and also an important part of the landscape in Jiuzhaigou. Primarily distributed in the Rize Valley, the Shuzheng Valley and their branches, it stretches for around 30 km intermittently and covers 2.44 km 2 .…”
Section: Study Areamentioning
confidence: 99%
“…Research has found that sulphate can slow down the nucleation crystallization of calcium carbonate and alter the crystal shapes as well as surface property. When concentrations of sulphate and nitrate in the solution lower, the calcite saturation index (SI C ) rises, contributing to the deposition process [38,70,71]. Except for inorganic ions, it is generally believed that dissolved organic matter (DOM) or dissolved organic carbon (DOC) is essential to travertine deposition.…”
Section: Correlation Analysis On Color Of the Blue Karst Lakes And Thmentioning
confidence: 99%